Focus Group Discussion (FGD) dengan Interprofessional Education (IPE) sebagai Alternatif Peningkatan Pengetahuan Tenaga Kesehatan tentang Kontrasepsi Oral dan Suntik di Kota Bandung - Ikhwan Yuda Kusuma; Doni Anshar Nuari; Kusnandar Anggadiredja (Universitas Muhammadiyah Surakarta, 2019)
The drop out rate of contraceptive use in Indonesia until 2016 still high at 25.7% of the government's target of 24%, this the optimization of the performance of health personnel should be improved, especially regarding health personnel knowledge about the use of oral and contraceptives which is the largest user in the city of Bandung. One of the efforts to improve the quality of family planning programs, through increasing the competence of health workers called Interprofessional Education (IPE). The purpose of this study was to identify the level of knowledge of health personnel at the health center regarding oral and injection contraceptives between professions with IPE in Bandung. This research used an experimental method with the type of group pre-posttest design. Data were analyzed using the Wilcoxon rank test from a questionnaire on health personnel's knowledge about oral and injection contraceptives on IPE before, and after Focus Group Discussion (FGD). The results showed there was an increase in the level of knowledge in 152 health personnel, a decrease in the level of knowledge in 5 health personnel, and no change in the four health personnel. Focus Group Discussion (FGD) through Interprofessional Education (IPE) was proven to significantly increase knowledge about oral contraceptives and injections on health personnel at the Health Center.